â€œCOLLABORATIVE GOVERNANCEâ€ PEMBANGUNAN KAMPUNG WISATA HERITAGE KAYUTANGAN KOTA MALANG - Rahmat Rahmat (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The Government of Malang keep striving to strengthen the tourism sector and increased collaboration with the community and related stakeholders. One form of collaboration between the Malang City Government, Pokdarwis, and the community is related to the implementation of the construction of the Kayutangan heritage tourism village.Â In the governance of the Regional Government, as a form of work program for the development of the tourism sector in thematic villages in collaboration with the community through the role and function of the Sports and Tourism Youth Office to strengthen and increase regional income properly through the tourism sector and carry out regional promotion to local and foreign tourists supervision of tourism development programs carried out by the Malang City Government, Pokdarwis, Society.